Local content law and practice: The case of the oil and gas industry in Ghana - Charles Godfred Ackah; Asaah S. Mohammed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Local content and local participation policy and legislation have come to stay in Ghana's oil and gas industry. The policy and legislation have been described largely as adequate, promising, and necessary to promote local content and local participation in the oil and gas industry. Implementation of the policy and legislation has, however, produced mixed results, according to industry stakeholders and researchers. Evidence on the ground suggests some level of compliance by international oil companies to implement the policy and legislation on local content. Some Ghanaian companies have been awarded contracts to provide essential services and goods to these companies during exploration and production. Several factors, however, militate against effective implementation of the policy and legislation. Notable among these are the low capacity of local firms, discrimination against local firms by international oil companies through vertical integration, and the weak regulatory capacity of the Petroleum Commission to enforce local content implementation. Vigorous capacity building of local firms, affirmative actions for local firms and employees, and legislative reviews are recommended to enhance the implementation of local content and local participation in Ghana's oil and gas industry.
Keywords: L71; L52; L78; Q34; 330; local content; law; practice; oil and gas; Ghana